Differences in Learning Outcomes of Islamic Religious Education Using Google Classroom and Conventional Models - Nurlaili Amin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of the study was to determine the differences in learning outcomes of Islamic education subject using Google Classroom and conventional class in grade VII SMP Negeri 8 Kota Bengkulu. The research method used was a quasi-experiment. The experimental class was given treatment used Google Classroom, while the control class still used conventional method. The populations were 211 students and the samples were 70 students that consist of two classes. Data were collected through tests, in terms of pre and posttests. The data analysis were conducted by using descriptive statistics and t-test. The result of the study was that the use of the Google Classroom model was considered as satisfactory with average score of 83.66 so it gave positive results. Then, the use of conventional class result was relatively low with an average score of 76.54. Based on the Independent Sample T-test obtained by Sig. (2-tailed) values of 0.000 < 0.05, it can be concluded that there was a difference in the average student learning outcomes between the Google Classroom and the conventional model.